"Aesthetic" in modern socio-cultural practices - V. S. Grytsenko (Ukrainian Cultural Studies, 2021)
The article is devoted to the fundamental problems of human philosophy and, at the same time, to the philosophy of culture as a product of its spiritual movement. Presented in modern science by separately developed theoretical discourses, in reality the aesthetic and cultural aspects are in relation of continuous interdependence, associated with the development of their generic basis – the human core of essence. The concept of aesthetics, which owes its emergence to the activity-based approach to the analysis of human essence, the understanding of the aesthetic and the moral as fundamental activities as the basis and conditions of human creation, suffers from unjustified reduction. Formed in the bosom of philosophical-anthropic universals, the culture studies, which should have been a methodologically analytical platform, a tendency towards factuality, moving to fleeting meanings, has revealed. This affected the optics of the aesthetic vision: the projection of its consideration became actual artistic practices, taken from the perspective of artistic instrumental form formation, abstracted from the defining human-motivated meaning. Left "off screen", it brings the analysis of contemporary artistic realities to superficial ones, to a simple statement of their sociocultural certainty and differences from what was known previously. The very life of the "aesthetic" – a condition and measure of the human essence development – provides such studies incapable of true expertise, primarily of determining the actual cultural weight of the artistic and aesthetic phenomenon and the prospects of its future existence. The urgency of recognizing this problem and its obligatory subsequent solution is one of the urgent tasks of culture studies on the way to its ultimate establishment as the center of humanitarian values. The understanding of the "aesthetic" as a human-forming condition necessarily expands the space of its cultural examination as well. It encompasses a bunch of actions and inner movements carried out in a human way. Moreover, the world of art needs to be taken into account when studying the presence of aesthetics in the general sphere of sociocultural practices. Whereas art as an aesthetic phenomenon is homogeneous in relation to the aesthetic, in the extra-artistic sphere the aesthetic gets into a homogeneity of a different order, namely into the root structure of the essential human self-development.